Bursty magnetic reconnection at Saturn's magnetopause. Issue 6 (21st March 2013) - Badman, S.V.; Masters, A.; Hasegawa, H.; Fujimoto, M.; Radioti, A.; Grodent, D.; Sergis, N.; Dougherty, M.K.; Coates, A.J.
<x xml:space="preserve">Abstract</x> [1] We infer the evolution of magnetopause reconnection from simultaneous in situ magnetopause crossings and auroral observations by Cassini on 19 July 2008. Depending on the magnetosheath field, it proceeds from (i) the high‐latitude lobe, producing a cusp spot in the aurora, to (ii) lower latitude but north of Cassini, evidenced by an enhancement of the pre‐noon auroral arc and escape of magnetospheric electrons during a long boundary layer traversal, to (iii) bursts of reconnection south of Cassini, resulting in bifurcations of the near‐noon auroral oval, escape of magnetospheric electrons, and a short boundary layer encounter. The conditions under which the auroral bifurcations associated with this bursty reconnection were observed were examined for this and three other examples. The magnetosphere was strongly compressed with a high magnetosheath field strength in every case. We conclude that reconnection can proceed at different locations on the magnetopause, depending on the local magnetic shear and plasma β conditions, and bursty reconnection occurs when the magnetosphere is strongly compressed and can result in significant solar wind‐driven flux transport in Saturn's outer magnetosphere.